The restraints of performance bond claims in construction industry [electronic resource] - Poh, Grace Chieng Ling, 1988- (2012)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2012